2021
DOI: 10.1016/j.molcel.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of protein-RNA interactions in SARS-CoV-2-infected cells reveals key regulators of infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19. SARS-CoV-2 relies on cellular RNA-binding proteins (RBPs) to replicate and spread, although which RBPs control its life cycle remains largely unknown. Here, we employ a multi-omic approach to identify systematically and comprehensively the cellular and viral RBPs that are involved in SARS-CoV-2 infection. We reveal that SARS-CoV-2 infection profoundly remodels the cellular RNA-bound proteome, which includes wide-ranging effects on RN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 92 publications
9
133
1
Order By: Relevance
“…It is important to note that two stress granule proteins, G3BP1 and G3BP2, were most consistently identified in other studies [ 4 , 5 , 6 , 7 , 8 , 15 , 26 , 27 , 28 , 29 ]. G3BP1 and G3BP2 are downregulated during SARS-CoV-2 infection, and inhibition of stress granule formation by the N protein indicates that the N protein is involved in suppressing the host immune response to favour virus replication [ 5 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that two stress granule proteins, G3BP1 and G3BP2, were most consistently identified in other studies [ 4 , 5 , 6 , 7 , 8 , 15 , 26 , 27 , 28 , 29 ]. G3BP1 and G3BP2 are downregulated during SARS-CoV-2 infection, and inhibition of stress granule formation by the N protein indicates that the N protein is involved in suppressing the host immune response to favour virus replication [ 5 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to viral proteins, it was shown that SARS-CoV-2 RNA directly and specifically binds and/or modulates a broad network of human proteins in infected human cells [178], and host mitochondria serve as an organelle platform for anti-SARS-CoV-2 immunity [179]. Approximately one-third of the cellular RNA-binding proteins (RBPs) are remodeled upon SARS-CoV-2 infection, and inhibition of these RBPs impairs SARS-CoV-2 infection [180].…”
Section: Virus-host Interaction and Exploitation Of The Cellular Machinerymentioning
confidence: 99%
“…Transcriptomic analysis and RBP knockdown experiments further identified eight pro-viral RBPs and 17 anti-viral RBPs that regulate viral RNA replication [ 131 ]. A recent study by Kamel et al employed UV crosslinking-based comparative RNA interactome capture (cRIC) and viral RNA interactome capture (vRIC) to study cellular and viral proteins that are altered upon SARS-CoV-2 infection in epithelial human lung cancer cells (Calu-3) [ 132 ]. Similar to the observation from Flynn et al, this study also describes the lower efficiency but higher specificity of UV crosslinking compared to formaldehyde crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…This further explains why some proteins linked to viral RNA metabolism (within ORF1a/b) could not be identified by the vRIC approach used in this study. Their analysis revealed that SARS-CoV-2 remodels the cellular RNA-bound proteome (RBPome), including proteins that play a crucial role in viral life cycle, RNA metabolism, and anti-viral response [ 132 ]. The study identified 809 proteins enriched with RNA-binding domains, out of which 335 RBPs demonstrated a significant fold change at 24 h post infection [ 132 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation